The Effect of Salary and Working Period on Employees Performance at Ued-Sp Bengkalis Sub-District - Nur Afiza (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
One of the factors that affect the level of organizational success is employee performance. Every company always expects its employees to have achievements, because employees who excel will provide optimal contributions to the company. This research is focused on the influence of salary and working period on employee performance. The purpose of this study was to determine the effect of salary on employee performance at UED-SP Bengkalis District, the effect of tenure on employee performance at UED-SP Bengkalis District. The effect of salary and tenure on employee performance in UED-SP Bengkalis District. The method used in this research is to use a questionnaire. While the data analysis method used is descriptive statistics, classical assumption test, correlation analysis,Linear Regression Analysis. Based on the results of the F test in Table 4.16, it can be seen that Fcount is 22,908 with a value of Ftable 3.19. So the value of Fcount> Ftable or 22,908 > 3.19 and significant level 0.000 <0.05 so that H0 is rejected and H1 is accepted. Can It can be concluded that the variable salary (X1) and the variable working periode (X2) Simultaneously a significant effect on the performance of employees of UED-SP Bengkalis District.Therefore the institution must pay attention to the welfare of its employees by adjusting employee salaries, in addition to providing other compensation, for example by providing health insurance, safety guarantees, work leave guarantees, vacation bonuses, etc. employee performance through training, so that employees have a lot of experience in the field of work. We recommend that you do and use automatic timekeeping tools and optimize the performance of existing employees by adding tasks and responsibilities that form a function of monitoring the employee's attendance.